Treatment of Tricuspid Regurgitation With the FORMA Repair System - Perlman, Gidon Y.; Dvir, Danny (Frontiers in Cardiovascular Medicine, 2018)
Background: Tricuspid regurgitation (TR) is common and undertreated as the risk of surgery is high in this patient population. Transcatheter devices offer treatment with a lower procedural risk. The FORMA Tricuspid Valve Therapy system (Edwards Lifesciences) will be reviewed here. Device Description: The system combines a spacer placed in the regurgitant orifice and a rail, over which the spacer is delivered, that is anchored to the endocardial surface of the RV. The spacer provides a surface for leaflet coaptation. Outcomes: Eighteen compassionate care patients and 29 patients included in the US EFS trial are reviewed. Patients were elderly (76 years) and high risk (Euroscore 2 was 9.0 and 8.1%, respectively). There were 2 procedural failures in both groups. Mortality at 30 days was 0% in the compassionate group and 7% in the EFS trial. TR was reduced in both groups; 2D/3D EROA 2.1 ± 1.8 to 1.1 ± 0.9 cm2 in the EFS trial and vena contracta width 12.1 ± 3.3 to 7.1 ± 2.2 mm. Symptomatic improvement was seen in both groups; the proportion of patients in NYHA class III/IV decreased from 84 to 28% at 30 days in the EFS group, and from 94 to 21% at 1 year, in the compassionate group. Conclusions: Reduction of TR with FORMA system is feasible and sustained. Despite residual TR post-procedure, the significant relative reduction in TR severity contributes to substantial clinical improvements in patients with a FORMA device in place.